Effects of N-methyl-N-nitrosourea on seed germitantion of Stevia rebaudiana = Kesan N-Metil-N-Nitrosourea pada percambahan biji benih stevia rebaudiana - Ahmad, Lyena Watty Zuraine; Zainuddin, Zarina; Osman, Mohamad; Mohamad, Azhar; Jaafar Sidek, Norrizzah (Penerbit UKM Press, 2019)
Stevia rebaudiana is a unique plant that contains non-caloric natural sweetener and has gained much interest among Malaysians. In this study, the effect of different concentrations of N-methyl-N-nitrosourea (MNU) was assessed in inducing mutation in Stevia seeds to produce genetic variations, which is valuable for crop improvement. Stevia seeds were soaked in six concentrations of MNU (0.0, 0.13, 0.25, 0.38, 0.50, and 1.00 mM) for four different durations (15, 30, 45, and 60 min) at room temperature. As a result, application of MNU reduced the germination percentage and germination rate of Stevia seeds as compared to the control group. Prolonged exposure to the highest concentration of MNU recorded the lowest percentage of germination (2.5 ± 1.4%) and the lowest germination rate (0.21 ± 0.16). Tricots were observed among seedlings treated with 0.13, 0.38 and 1.0 mM of MNU for 30 min. Presence of seedlings with albino colour proved the mutagenic effect of MNU on Stevia genome. Based on the percentage of seedlings with chlorophyll mutation, the most effective and ef cient mutagenic treatment to induce mutation was 60 min in 0.25 mM of MNU. ******************************************************** Stevia rebaudiana ialah tumbuhan unik yang mengandungi pemanis semula jadi tanpa kalori yang menarik minat ramai rakyat Malaysia. Dalam kajian ini, kesan kepekatan N-metil-N-nitrosourea (MNU) dikaji dalam mendorong mutasi pada biji Stevia untuk menghasilkan variasi genetik yang berguna untuk pembaikan tanaman. Biji Stevia direndam dalam larutan MNU dengan enam kepekataan berlainan (0.0, 0.13, 0.25, 0.38, 0.50 dan 1.00 mM) untuk empat tempoh yang berbeza (15, 30, 45 dan 60 minit) pada suhu bilik. Penggunaan MNU didapati mengurangkan peratus dan kadar percambahan biji Stevia berbanding dengan kumpulan kawalan. Pendedahan berpanjangan kepada kepekatan MNU yang tertinggi mencatatkan peratusan percambahan terendah (2.5 ± 1.4%) dan kadar percambahan terendah (0.21 ± 0.16). Anak benih dengan trikot dicerap pada kumpulan yang dirawat dengan 0.13, 0.38 dan 1.0 mM MNU selama 30 minit. Kehadiran anak benih dengan warna albino membuktikan kesan mutagen MNU pada genom Stevia. Berdasarkan peratusan anak benih dengan mutasi klorofil, rawatan mutagenik yang paling berkesan dan cekap untuk merangsang mutasi ialah selama 60 minit dalam 0.25 mM MNU.